Fungsi alat batu dari Situs Gua Arca, Pulau Kangean, Jawa Timur - Rahfi Muhammad (Balai Arkeologi Yogyakarta, 2021)
This article examines the functions of stone tools from Gua Arca site, Kangean Island, Madura, Province of East Java. This research aims to determine the functionality of the stone tools through tool-type and use-wear analysis and compare them with the experimental result from the experts. The knowledge of the stone tools functions was build by classifying the stone tools into a particular type that depends on edge attributes, including the edge localization and edge angle. Hereafter, the stone tools sorted to separate which of the 142 stone tools have a use-wear indication. The sorting result showed that ten stone tools have several traces that indicate the usage of the tools. Hereafter, the use-wear analysis conducted on these ten tools was observed and recorded according to the use-wear form, localization, and distribution on the tool edges. After that, the results on tool-type and use-wear analysis compared with the experts’ experiments. It explained the correlation between use-wear with the tools activities and the worked materials. The similarities between the use-wear forms from the experts’ experiments result and stone tools use-wear forms from the Gua Arca site used to interprate its functions. Based on the research conducted, it is estimated stone tools of Gua Arca were used for woodworking and food processing.